A new cryptic species of Echinostoma (Trematoda: Echinostomatidae) closely related to Echinostoma paraensei found in Brazil - Valadão, Marisa C.; Alves, Philippe V. [UNESP]; López-Hernández, Danimar; Assis, Jordana C. A.; Coelho, Paulo R. S.; Geiger, Stefan M.; Pinto, Hudson A. (Cambridge University Press (CUP), 2023)
Echinostoma paraensei, described in Brazil at the end of the 1960s and used as a biological model for a range of studies, belongs to the 'revolutum' complex of Echinostoma comprising species with 37 collar spines. However, molecular data are available only for a few isolates maintained under laboratory conditions, with molecular prospecting based on specimens originating from naturally infected hosts virtually lacking. The present study describes Echinostoma maldonadoi Valadão, Alves & Pinto n. sp., a species cryptically related to E. paraensei found in Brazil. Larval stages (cercariae, metacercariae and rediae) of the new species were found in the physid snail Stenophysa marmorata in the State of Minas Gerais, Brazil, the same geographical area where E. paraensei was originally described. Adult parasites obtained experimentally in Meriones unguiculatus were used for morphological (optical microscopy) and molecular [28S, internal transcribed spacer (ITS), nad1 and cox1] characterization. The morphology of larval and adult parasites (most notable the small-sized dorsal spines in the head collar), associated with low (0-0.1%) molecular divergence for 28S gene or ITS region, and only moderate divergence for the mitochondrial cox1 gene (3.83%), might suggest that the newly collected specimens should be assigned to E. paraensei. However, higher genetic divergence (6.16-6.39%) was found in the mitochondrial nad1, revealing that it is a genetically distinct, cryptic lineage. In the most informative phylogenetic reconstruction, based on nad1, E. maldonadoi n. sp. exhibited a strongly supported sister relationship with E. paraensei, which may indicate a very recent speciation event giving rise to these 2 species.
Keywords: Brazil; cryptic species; Echinostoma; integrative taxonomy; phylogeny